Engineering of Hollow Core–Shell Interlinked Carbon Spheres for Highly Stable Lithium–Sulfur Batteries - Sun, Qiang; He, Bin; Zhang, Xiang-Qian; Lu, An-Hui (ACS nano, 2015)
We report engineered hollow core–shell interlinked carbon spheres that consist of a mesoporous shell, a hollow void, and an anchored carbon core and are expected to be ideal sulfur hosts for overcoming the shortage of Li–S batteries. The hollow core–shell interlinked carbon spheres were obtained through solution synthesis of polymer spheres followed by a pyrolysis process that occurred in the hermetical silica shell. During the pyrolysis, the polymer sphere was transformed into the carbon core and the carbonaceous volatiles were self-deposited on the silica shell due to the blocking effect of the hermetical silica shell. The gravitational force and the natural driving force of lowering the surface energy tend to interlink the carbon core and carbon/silica shell, resulting in a core–shell interlinked structure. After the SiO2 shell was etched, the mesoporous carbon shell was generated. When used as the sulfur host for Li–S batteries, such a hierarchical structure provides access to Li+ ingress/egress for reactivity with the sulfur and, meanwhile, can overcome the limitations of low sulfur loading and a severe shuttle effect in solid carbon-supported sulfur cathodes. Transmission electron microscopy and scanning transmission electron microscopy images provide visible evidence that sulfur is well-encapsulated in the hollow void. Importantly, such anchored-core carbon nanostructures can simultaneously serve as a physical buffer and an electronically connecting matrix, which helps to realize the full potential of the active materials. Based on the many merits, carbon–sulfur cathodes show a high utilization of sulfur with a sulfur loading of 70 wt % and exhibit excellent cycling stability (i.e., 960 mA h g–1 after 200 cycles at a current density of 0.5 C).